COMING TO TERMS WITH A PAGAN PAST: THE STORY OF ST ERKENWALD - Schustereder, Stefan (Studia Anglica Posnaniensia, 2014)
The poem of St Erkenwald and his encounter with the body of a pagan judge preserved in a tomb underneath St Paul's Cathedral has never provoked an intense scholarly discussion. During the past two decades, however, the poem has altogether lost the scarce attention it used to receive. This is surprising in regards to its outstanding quality but also because of a number of peculiar characteristics the text has in comparison with other works written during the Middle Ages. Arguing for the importance of the historical details provided by the poem, my article takes a number of these peculiarities into account and suggests a new reading of the poem. In this approach, I do not dismiss the major topics of the earlier scholarly discussions, mostly focused on the poem's theological and stylistic topics or its presumed sources. My article rather presents an additional reading from the perspective of a literary history, thus arguing that the poem of St Erkenwald can be placed within a discourse tradition to which a number of earlier authors contributed, the most famous among them being the Venerable Bede. While the poem addresses a variety of theological and stylistic topics and is of course influenced by its contemporary religious and social developments, it also contributes to one of the fundamental problems of English identity in the Middle Ages: coming to terms with a pagan origin.